THE NEXUS BETWEEN SECURITY AND DEVELOPMENT: AN INTERROGATION OF THE MENACE OF UNKNOWN GUNMEN (UGM) IN SOUTHEAST OF NIGERIA - Ibekwe, Emmauel Ogueri (African Journal of Social and Behavioural Sciences, 2024)
This research looked at the nexus between security and development by interrogating the activities of unknown gunmen. The study reviewed the activities of the unknown gunmen on the economic and social development of the southeastern part of Nigeria. The functionalist theory/perspective was adopted as the framework for analysis. The secondary method of data collection was used to assemble data from documents, which was analysed qualitatively This finding showed that the menace of unknown gunmen has in diverse ways undermined both economic and social development in the southeast region of Nigeria. This paper found out that the activities of these non-state actors (unknown gunmen) have increased the poverty level, disrupted/closed a number of business/commercial activities, destroyed both public and private infrastructures, and undermined educational and general development in the area. The study recommended more government commitment towards insecurity exploring kinetic and non-kinetic approaches in finding a solution to this problem, adoption of ICT enhanced surveillance equipment, strengthening of security agencies, and encouraging more synergy among security agencies in their joint operations in this area, while leveraging on community policing for intelligence that may lead to the identification of the sympathizers and sponsors of the unknown gunmen.